The tethered aminohydroxylation (TA) of cyclic allylic carbamates. - Donohoe, T; Johnson, P; Cowley, A; Keenan, M (2002)
The tethered aminohydroxylation of cyclic allylic carbamates is described using catalytic amounts of potassium osmate. The mechanism of reaction involves formation of an imido-osmium complex which adds intramolecularly to alkenes with complete control of both regio- and stereoselectivity: the formation of syn-aminodiol motifs is now straightforward using this chemistry. Proof of the mechanism was obtained with an X-ray crystal structure of an azaglycolate osmate ester intermediate.